Application of Google Maps API on Smart City for Searching Distance Nearby Health Facilities in Bangkalan - ela nur azizah; achmad jauhari; yoga dwitya pramudita (International Journal of Science, Engineering, and Information Technology, 2016)
Health facility is a facility which engaged in health in an effort to provide services from government and society to inform about health, prevention of disease, treatment, and bring back the sicks to their main environment. The health informaion which is provided by Google Maps is not complete yet. So, the problem that arises is the media that provide health information is still small. And society in Bangkalan cant reach the health information in overall. That problem can solve with an aplication which is build by Framework Codeigniter and Google Maps API. This application can accomodate and provide health data facility completely. So the society in Bangkalan can search by their own self about location with the nearest distance and know all about health information. Such like health facility, the addresses, and doctor's schedules in hospital and community health centre. The applocation which has been build is effective to help society to know all location and information about health in Bangkalan. This proven by quality of this application to 10 respondent with resultd 77,3%